Identifikasi Manajemen Pengendalian Penyakit ISPA di Wilayah Kerja Puskesmas Purwoharjo Kabupaten Pemalang - Dewi Nugraheni; Yulis Indriyani; Sabila, Arifah Mutiara; Adelia Solecha Putri; Anis Tiara Sari Wihar (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Acute Respiratory Tract Infection (ARI) is one of the significant health challenges that still occurs frequently, especially in children aged 0 to 5 years. This study aims to understand how ARI disease control is managed in the Purwoharjo Health Center work area, Pemalang Regency. The method used in this research is qualitative with a case study approach and descriptive analysis. Data was collected through in-depth interviews with health workers directly involved in the implementation of the ARI control program. Findings from the study show that the incidence of ARI, including pneumonia in children under five, is still quite high due to the limited number of health workers, low public awareness, and unfavorable environmental conditions. ARI control has been carried out in two ways, namely activities within health facilities (examination and hospitalization) and activities outside facilities (home visits, posyandu, and counseling). Periodic evaluations conducted every three months show a 25% reduction in ARI incidence,p although further efforts are needed to reach the target of eliminating cases. The conclusion of this study highlights the importance of inter-sectoral cooperation, public health education, and routine monitoring in reducing ARI incidence. It is hoped that the ARI prevention and control program can be continuously improved through